A speech-based distributed architecture platform for an intelligent ambience. (October 2018) - Kos, Marko; Rojc, Matej; Žgank, Andrej; Kačič, Zdravko; Vlaj, Damjan
Highlights: A platform for intelligent ambience with several HMI services is proposed. For mobile application within the ambience robotic unit Genesis is presented. Distributed architecture provides flexibility and extended connectivity. Mobile unit Genesis proves to be highly manoeuvrable and easy to operate. Abstract: In the paper, a speech-based platform for intelligent ambience and/or supportive environment applications is presented. The platform has a distributed architecture, which enables extended connectivity and support for multiple intelligent ambience services. The mobile unit Genesis is an integral part of the distributed platform, enabling interaction between several users and the environment. Furthermore, the sophisticated client/server platform's architecture incorporates robust speech recognition and text-to-speech synthesis engines for more natural human-machine interaction between users and the mobile unit Genesis. Both engines are multilingual oriented. Although the whole system is developed for the Slovenian language, it can be quickly adapted for other languages when appropriate language resources are available. With high speaker independent speech recognition accuracy and low command-to-operation delay, Genesis proves to have good manoeuvrability and it is easy to operate even by a non-experienced operator. Graphical abstract: Image, graphical abstract